The world of chaos - Bolotin, Yu.L .; Yanovsky, V.V. (Вопросы атомной науки и техники, 2007)
The present paper is devoted to discussion of origins of the modern paradigm of deterministic chaos: the transition from the older philosophy understanding chaos as a result of uncontrolled external effects to the theory based on internal mechanism of the chaos appearance in nonlinear systems. The report briefly presents the main steps of research in framework of new approach. Success of the new approach is demonstrated on two important dynamical systems – billiards and atomic nuclei. Робота присвячена обговоренню природи сучасної парадигми детермінованого хаосу: переходу від старої філософії розуміння хаосу, як результату неконтрольованих впливів на систему до теорії внутрішнього механізму появи хаосу в нелінійних системах. Доповідь стисло знайомить з головними етапами досліджень у рамках нового підходу. Досягнення цього нового підходу демонструються на двох важливих системах – більярдах та атомних ядрах. Работа посвящена обсуждению природы современной парадигмы детерминированного хаоса: перехода от старой философии понимания хаоса как результата неконтролируемых воздействий на систему к теории внутреннего механизма появления хаоса в нелинейных системах. Доклад кратко знакомит с основными этапами исследований в рамках нового подхода. Достижения этого нового подхода демонстрируются на двух важных системах – бильярдах и атомных ядрах.